Seamless Healthcare Monitoring Advancements in Wearable, Attachable, and Invisible Devices - Tamura, Toshiyo; Chen, Wenxi; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book shares the knowledge of active and prestigious worldwide researchers and scholars in the field of healthcare monitoring as authors investigate historical developments, summarize latest advancements, and envision future prospects on wearable, attachable, and invisible devices that monitor diverse physiological information. The coverage of the book spans multiple disciplines, from biomechanics, to bioelectricity, biochemistry, biophysics and biomaterials. There is also wide coverage of various physical and chemical quantities such as electricity, pressure, flow, motion, force, temperature, gases, and biomarkers. Each chapter explores the background of a specific monitoring device, as well as its physical and chemical principles and instrumentation, signal processing and data analysis, achieved outcomes and application scenarios, and future research topics. There are chapters on: Electrocardiograms, electroencephalograms, and electromyograms Measurement of flow phenomenon Latest wearable technologies for the quantification of human motion Various forms of wearable thermometers Monitoring of gases and chemical substances produced during metabolism...and more! This book is appropriate and accessible for students and scientists, as well as researchers in biomedical engineering, computer engineers, healthcare entrepreneurs, administrative officers, policy makers, market vendors, and healthcare personnel. It helps to provide us with insights into future endeavors, formulate innovative businesses and services, and will help improve people's health and quality of life.
Part 1. Bioelectric Signals -- Chapter 1. Electrocardiogram -- Chapter 2.Electroencephalogram -- chapter 3.Electromyogram -- Part II. Pressure Signals -- Chapter 4.Blood Pressure -- Chapter 5.Ballistocardiogram -- Part III Pulse and Flow -- Chapter 6.Photoplethysmogram -- chapter 7.Ultrasonic Doppler Velocity and Imaging -- Part 4 Motion and Force -- Chapter 8.Wearable Units -- Chapter 9.Smart Textile Suit -- Part 5.Temperature -- Chapter 10. Body Temperature, Heat Flow and Evaporation -- Part 6.Gases and Biomarkers -- Chapter 11.SpO2 and CO2 -- Chapter 12.Chemical Substances -- Part 7.Nutrition and Energy Expenditure -- Chapter 13.Dietary Intake -- Chapter 14.Physical Activity.
Keywords: Biomedical engineering; Electronic circuits; Signal processing; Microtechnology; Microelectromechanical systems; Public health administration; Biotechnology; Biomedical Engineering and Bioengineering; Electronic Circuits and Systems; Signal, Speech and Image Processing; Microsystems and MEMS; Health Administration; Biotechnology